2018
DOI: 10.23928/foldt.kozl.2018.148.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Nyílt rendszerű magmás folyamatok: magmakeveredés, kristálycsere és kumulátum-recirkuláció nyomai a Ditrói alkáli masszívumban (Orotva, Románia)

Abstract: A Tarniţa Komplexum a Keleti-Kárpátokban (Románia) felszínre bukkanó Ditrói alkáli masszívum északi területének jellemző ultramafikus és mafikus kőzetegyüttese. A komplexum Ny-i részén, az Orotva-patak és a Felső-Pietrăriei-patak összefolyásánál található mélységi magmás kőzettestben kialakított mesterséges feltárás egyedülálló betekintést enged az egykori magmatározóban zajlott, több magma között lejátszódott keveredési és elegyedési folya matokba, illetve az új magmabenyomulások során feltépett, korábban kik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…(Fig. 2A) near the confluence of the Pietrăriei de Sus and Jolotca Creeks (Heincz et al 2018), no other intrusive contacts were found in this region. Mingling structures of diorite (s.l.)…”
Section: Geologic Settingmentioning
confidence: 89%
See 1 more Smart Citation
“…(Fig. 2A) near the confluence of the Pietrăriei de Sus and Jolotca Creeks (Heincz et al 2018), no other intrusive contacts were found in this region. Mingling structures of diorite (s.l.)…”
Section: Geologic Settingmentioning
confidence: 89%
“…Previous studies have interpreted the felsic suite of the northern part of the DAM as a homogeneous, uniform unit of the massif (e.g., Jakab 1998; Kovács & Pál-Molnár 2005). Nevertheless, recent investigations have suggested that the felsic rocks were formed in an open-system magmatic environment (e.g., Batki et al 2018;Heincz et al 2018;Ódri et al 2020;Kiri et al 2022). A detailed petrographic study of the felsic suite in the northern area of the DAM revealed microtextural features (e.g., mafic clots, plagioclase crystals in synneusis relation, adjacent plagioclase feldspars with disparate zoning patterns, country rock xenoliths) indicative of dynamic magmatic conditions (e.g., crystal transfer and recycling, cumulate formation, magma mixing and mingling, as well as wall rock assimilation; Kiri et al 2022).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Pál-Molnár et al (2015a) revealed that accumulation of mafic minerals has played a crucial role in the petrogenesis of some rock types of the DAM (e.g., olivine-rich cumulate, amphibole-and pyroxene-rich cumulate, amphibole-rich cumulate). The existence of a hypothetic felsic cumulate pile in the massif has been proposed by Heincz et al (2018). Furthermore, Ódri et al (2020) presumed that some felsic rocks (e.g., syenite and quartz syenite) could have been formed by crystal accumulation as well.…”
Section: Central European Geologymentioning
confidence: 98%
“…Felsic rocks have been regardedboth at macro and micro-scaleas homogeneous, uniform units of the DAM throughout almost the entire research history of the massif. Recently, some studies (e.g., Batki et al, 2018;Heincz et al, 2018;Ódri et al, 2020) drew attention to distinct structural, textural and geochemical features, implying open-system processes that had operated during the formation of the examined felsic rocks. Application of in-situ geochemical analysis made a significant contribution to the appropriate interpretation of these rocks.…”
Section: Central European Geologymentioning
confidence: 99%
See 1 more Smart Citation